Teacher Performance in the 21st Century: Examining the Roles of Leadership, Self-Efficacy, Compensation, and Job Satisfaction - Puspitasari , Jerry; Sutarto , Joko; Pramono , Suwito Eko; Sutopo , Yeri (Journal of Ecohumanism, 2024)
The main purpose of this study is to examine the effect of leadership on teacher performance via self-efficacy and job satisfaction, a mediating variable, as well as compensation. Based upon an Indonesia study, the research engages a meta-analysis of these relationships for illuminating insights on optimizing teacher performance in educational environments. We collected data from a sample of 680 teachers 87% response rate and analyzed them using SmartPLS, the evaluation comparable to complex social science models. The results suggest that both self-efficacy and compensation affect teacher performance directly, respectively, through job satisfaction; principal leadership only has a significant direct effect on the dependent variable without being mediated by job satisfaction. These results may have implications for how intrinsic and extrinsic factors, motivation, rewards, and leadership styles influence faculty outcomes. The practical implications include a call for targeted teacher professional development and compensation policies that are more equitable and effective educational leadership practices to improve teaching performances, which will in turn favorably impact the quality of education generally.